RESPON RUSA TIMOR TERHADAP PEMBERIAN PAKAN ALTERNATIF DI PENANGKARAN - Helly Fitriyanty; Burhanuddin Masy'ud; Agus Priyono Kartoko (Media Konservasi, 2014)
The aim of the research are to analyzed the silage quality, analyze feeding behaviour of timor deer in introduction of silage, to evaluation the effect of alternative feed that is elephant grass, elephant grass silage and waste farm silage (rice straw and banana trunk) to performance of timor deer, from palatability, average daily consumption, average daily gain and feed conversion. Experimental design used completely randomized design with three treatments and three repetition. The treatments were P1: 72% elephant grass and 28% elephant grass silage, P2: 65% elephant grass and 35% rice straw silage, P3: 54% elephant grass and 46% banana trunk silage. Addition 3% molases result good quality silage of elephant grass silage, rice straw silage and banana culm silage in term of physical and chemical characteristics. Timor deer in the captive gave a positive response to eating behaviour and adaptive to the silage as an alternative feed. Analysis of palatability with Manly's Alpha showed there was trend elephant grass silage and banana trunk silage have good palatability than rice straw silage. Analysis of Variance showed that the experiment feed (P1, P2 and P3) were not significantly different effect (p>0.05) to average daily consumption, average daily gain, and feed conversion, but the best feed conversion obtained from P3, so P3 (RGS+SBP) is considered more efficient and profitable than P1 (RGS+SRG) and P2 (RGS+SJP) in biological and economic technically and can be chosen as an alternative feed to Timor deer in the captive.  Keyword: Banana trunk, Elephant grass, Rice straw, Silage, Timor deer